Insights into the cellular trafficking of splice redirecting oligonucleotides complexed with chemically modified cell-penetrating peptides. - Hassane, F; Abes, R; Andaloussi, S; Lehto, T; Sillard, R; Langel, U; Lebleu, B (2011)
Conjugates of cell-penetrating peptides (CPP) and splice redirecting oligonucleotides (ON) display clinical potential as attested by in vivo experimentation in murine models of Duchenne muscular dystrophy. However, micromolar concentrations of these conjugates are required to obtain biologically relevant responses as a consequence of extensive endosomal sequestration following endocytosis. Recent work from our group has demonstrated that appending stearic acid to CPPs increases their efficiency and that the inclusion of pH titrable entities leads to further improvement. Moreover, these modified CPPs form non covalent complexes with charged ON analogs or siRNAs, which allows decreasing the concentrations of ONs by nearly one log. These modified CPPs and the parent peptides have been compared here in the same in vitro model in terms of cell uptake, trafficking and splicing redirection activity. The increased splicing redirection activity of our modified CPPs cannot be explained by differences in cell uptake but rather by their enhanced ability to escape from endocytic vesicles. Accordingly, a clear correlation between membrane destabilizing activity and splicing redirection was observed using a liposome leakage assay. Studies of cellular trafficking for the most active PF6:ON complexes indicate uptake by clathrin-mediated endocytosis using either FACS cell uptake or a splicing redirection functional assay. Acidification of intracellular vesicles and membrane potential were found important for splicing redirection but not for cell uptake. These results do confirm that the increased potency of PF6:ON complexes is not due to the use of a non endocytic route of cell internalization as proposed for some CPPs.